2013
DOI: 10.2146/ajhp120464
|View full text |Cite
|
Sign up to set email alerts
|

Comparative risk of bloodstream infection in hospitalized patients receiving intravenous medication by open, point-of-care, or closed delivery systems

Abstract: Use of POC-activated and closed systems for i.v. drug delivery was associated with a significantly reduced risk of hospital-acquired BSI compared with exclusive use of open systems in a large population of hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
6
0
2
Order By: Relevance
“…It also gives nurses more direct‐contact time with patients and their families, managing the many nursing activities such as attending to the basic care and psychosocial needs of patients, as well as coordination of care which may occur during administration of IV medications. In addition, the risk of blood stream infection is also shown to be lower with the use of the POC‐activated system …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also gives nurses more direct‐contact time with patients and their families, managing the many nursing activities such as attending to the basic care and psychosocial needs of patients, as well as coordination of care which may occur during administration of IV medications. In addition, the risk of blood stream infection is also shown to be lower with the use of the POC‐activated system …”
Section: Discussionmentioning
confidence: 99%
“…Manufacturer‐prepared RTU products and POC‐activated products are recommended by the Consensus Development Conference on The Safety of Intravenous Drug Delivery Systems as the preferred IV drug administration system . It was also shown that use of POC‐activated or RTU systems for IV drug delivery were associated with a significantly reduced risk of hospital‐acquired blood stream infection compared with the use of the traditional open system …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In fact, some fluids and drugs formulated for intravenous infusion can sustain the growth of microorganisms that may cause serious infectious complications. [15][16][17] Although intrinsic (i.e. from the manufacturer) infusate contamination is rare, high rates of extrinsic contamination 18 (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported lower risk of BSI [6e9], shorter length of stay (LOS) [6], and lower total hospitalization or treatment costs [8] for MCB vs. COM or other methods requiring manipulation of the PN mixture. Utilizing the Premier research database for discharges occurring in calendar years 2005e2007 inclusive, Turpin et al reported that the BSI infection rate for patients using pharmacy prepared compounded PN was 25.9% compared to 19.6% for patients using MCB [10].…”
Section: Introductionmentioning
confidence: 99%